2012
DOI: 10.5539/ijel.v2n1p97
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning: A Ubiquitous Learning Environment for Reading Comprehension

Abstract: Learning environments have turned to a hot discussion among language scholars. Very popular nowadays, blended learning is not a new concept. It enjoys the advantages of face-to-face classrooms and virtual learning. This study is an attempt to discover whether conventional or blended learning environments can better enhance the reading comprehension for EFL learners. 107 Iranian students majoring in English at Abadeh Islamic Azad University and Zand Institute of Higher Education in Shiraz were selected. A readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 11 publications
4
31
0
Order By: Relevance
“…Behjat et al (2012) described the goal of blended instruction, or sometimes referred to as hybrid education, as an avenue to teach the student cognitive independence, make education useful through modern technology, and establish the sustainability of the classroom for the future. As a result of this cohesive relationship, the benefits of blended learning are recognizable in student outcomes.…”
Section: Blended Instruction: a Viable Alternativementioning
confidence: 99%
“…Behjat et al (2012) described the goal of blended instruction, or sometimes referred to as hybrid education, as an avenue to teach the student cognitive independence, make education useful through modern technology, and establish the sustainability of the classroom for the future. As a result of this cohesive relationship, the benefits of blended learning are recognizable in student outcomes.…”
Section: Blended Instruction: a Viable Alternativementioning
confidence: 99%
“…As well as Teeter (1997) identified the impact of teaching with the Internet on the students' motivation to learn and increase their ability to debate and resolve duties, the results indicated to increase students' motivation, and inform them of a lot of sources, and improve their ability to debate and solve homework. Behjat, Yamini and Bagheri (2012) showed that the Iranian tertiary education contexts that blending traditional classroom instruction and technology can help learners excel in their reading comprehension.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Althoughstudents' gender had a significant effect on students' learning style preferences, it had no bearing on their satisfaction with web-based materials. Behjat, Yamini and Bagheri (2012) discovered in a study in the Iranian tertiary education context that blending traditional classroom instruction and technology can help learners excel in their reading comprehension. Al-Mansour and Al-Shorman (2009) studied the effect of computer-assisted instruction on Saudi university students' learning of English, and their findings indicated that the integration of technology into a traditional face-to-face class hada positive effect on the experimental groups' achievement.…”
mentioning
confidence: 99%